METODOLOGÍA CIENTÍFICA Y DESCRIPCIÓN EN UN CENTENAR DE REFRANES ESPAÑOLES - de Jaime Lorén, José María (Proverbium - Yearbook, 2018)
SCIENTIFIC METHODOLOGY AND DESCRIPTION OF ONE HUNDRED SPANISH SAYINGS. In the context of an investigation into the phenomenon of the description in the process of knowledge acquisition and dissemination of knowledge within the fields of his-tory of science, anthropology and philology, we conducted a study on the paremiological description research. In the same study we present the methodology developed through decades, based on trying to find the original sources of proverbs and sayings sententious, preferably researching the oldest paremiales collections (manuscripts, incunabula and classical sources), to gradually reach large modern collections. This way, we can approach the knowledge of the evolution of popular wisdom throughout the ages. The work of a small collection of sayings dealing description and scientific method (inductive and deductive) is attached.